First aid improves clinical outcomes in burn injuries: Evidence from a cohort study of 4918 patients. Issue 2 (March 2019) - Harish, Varun; Tiwari, Neha; Fisher, Oliver M.; Li, Zhe; Maitz, Peter K.M.
Highlights: Treating a burn wound with cool, running water for 20 min up to 3 h post injury improves clinical outcomes. Benefits are seen in reduction in wound depth, faster re-epithelialisation, and decreased skin grafting requirements. First study to conclusively prove advantages offered by first aid and the first to corroborate experimental evidence. Abstract: Background: Animal studies indicate treating burn injuries with running water (first aid) for 20 min up to 3 h post-burn reduces healing time and scarring. There is a lack of human data to support such a recommendation. The purpose of this cohort study was to assess the effect of first aid on clinical outcomes. Methods: Data was prospectively collected for patients with <10% total body surface area (TBSA) burns from 2007–2012. Multivariate regression analysis was used to determine the association of adequate first aid with four outcomes — wound depth, requirement for skin grafting, healing time (in non-grafted patients), and TBSA not grafted (in grafted patients). Adequate first aid was defined as the application of 20 min of cool, running tap water up to 3 h following the burn injury. Findings: 4918 patients were identified. Adequate first aid was received in 58.1% (2859) of patients. It was associated with a statistically significant reduction in burn wound depth (OR 1.39; 95% CI 1.24–1.55; P < 0.001) but was not associated with a reduction in TBSA (P = 0.86) or requirement for grafting (P = 0.47). In patients not requiring grafting, those who received adequate first aid were healed on average 10% (HR 1.10; 95% CI 1.03–1.18; P < 0.01) or 1.9 days faster (95% CI −2.9 to −0.9; P < 0.001). Adequate first aid in patients requiring grafting was associated with a 15% increase in TBSA that was not grafted (0.27%; 95% CI 0.01–0.52; P = 0.04). Interpretation: Adequate first aid with 20 min of running water is associated with improved outcomes. Benefits are seen in a reduction in wound depth, faster healing, and decreased grafting requirements. This has significant patient and health system benefits, and calls for promotion of 20 min of running water globally in burns care.